2020
DOI: 10.1126/sciadv.abb4848
|View full text |Cite
|
Sign up to set email alerts
|

Let more big fish sink: Fisheries prevent blue carbon sequestration—half in unprofitable areas

Abstract: Contrary to most terrestrial organisms, which release their carbon into the atmosphere after death, carcasses of large marine fish sink and sequester carbon in the deep ocean. Yet, fisheries have extracted a massive amount of this “blue carbon,” contributing to additional atmospheric CO2 emissions. Here, we used historical catches and fuel consumption to show that ocean fisheries have released a minimum of 0.73 billion metric tons of CO2 (GtCO2) in the atmosphere since 1950. Globally, 43.5% of the blue carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 48 publications
0
87
0
Order By: Relevance
“…If we further assume that most of these fishes are extracted from the shelf regions, and that the total air‐sea flux of carbon on the shelves is approximately ~ 0.25 Pg C yr −1 (Cai et al 2006; Laruelle et al 2010), then such an extraction represents over 8% of the total air‐sea carbon flux on the global continental shelf. A global analysis based on historical catches and fuel consumption examined the role of ocean fisheries in atmospheric CO 2 emissions, and concluded that these activities have released a minimum of 0.73 Gt CO 2 into the atmospheric since 1950 (Mariani et al 2020). However, for context, other sources of animal protein contribute significantly more CO 2 emission equivalents (livestock = 7.1 Gt CO 2 ‐equivalent yr −1 ) than global fisheries (Gerber et al 2013).…”
Section: Fish‐based Contributions To Carbon Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…If we further assume that most of these fishes are extracted from the shelf regions, and that the total air‐sea flux of carbon on the shelves is approximately ~ 0.25 Pg C yr −1 (Cai et al 2006; Laruelle et al 2010), then such an extraction represents over 8% of the total air‐sea carbon flux on the global continental shelf. A global analysis based on historical catches and fuel consumption examined the role of ocean fisheries in atmospheric CO 2 emissions, and concluded that these activities have released a minimum of 0.73 Gt CO 2 into the atmospheric since 1950 (Mariani et al 2020). However, for context, other sources of animal protein contribute significantly more CO 2 emission equivalents (livestock = 7.1 Gt CO 2 ‐equivalent yr −1 ) than global fisheries (Gerber et al 2013).…”
Section: Fish‐based Contributions To Carbon Fluxmentioning
confidence: 99%
“…Furthermore, because fishes provide other benefits to humans (nutrition, biodiversity, cultural, recreational, commercial), management decisions are currently made without understanding the trade‐offs and interdependencies between these uses, their impacts and fish‐based carbon flux (Martin et al 2016; Legge et al 2020). A recent global analysis concluded that overexploitation of fish stocks could reduce the contribution of marine fishes, particularly in carcass deadfall, to blue carbon sequestration over time (Mariani et al 2020). The economic value of carbon storage reduced by fisheries in the eastern tropical Pacific was estimated as $12.9 billion yr −1 (Martin et al 2016), while the cost of predicted declines in the biological carbon pump in the North Atlantic by 2100 due to increasing carbon emissions was estimated at between $170 and $3000 billion in mitigation costs, and $23 and $401 billion in adaptation costs (Barange et al 2017).…”
Section: Actionable Recommendationsmentioning
confidence: 99%
“…Although not a focus of this review, the removal of vertebrate species by benthic and pelagic fisheries could influence the mass of OC stored in seabed sediments (Pershing et al 2010, Atwood et al 2015, Mariani et al 2020). The emerging field of “fish carbon” describes the contribution of vertebrate fauna to OC storage and sequestration within seabed sediments from defecation, pelagic mixing, bioturbation, trophic interactions and deadfall (Trueman et al 2014, Turner 2015, Saba et al 2021).…”
Section: Links Between Seabed Sediment Oc and Mobile Demersal Fishingmentioning
confidence: 99%
“…Although the magnitudes of effect are poorly resolved, the reduction in population size and average body size of marine vertebrates that results from over-harvest, is expected to reduce the amount of carbon exported to the seabed (Fig. 1f) (Pershing et al 2010, Trueman et al 2014, Atwood et al 2015, Mariani et al 2020). For example, since 1950, the combined catch of Tuna, Mackerel, Shark and Billfish is estimated to have prevented approximately 21.8 Mt of OC being stored in seabed sediments (Mariani et al 2020).…”
Section: Links Between Seabed Sediment Oc and Mobile Demersal Fishingmentioning
confidence: 99%
See 1 more Smart Citation